Exploring the usability of platforms for individuals with visual impairments: a systematic literature review - Adnan, Fahrobby; Putra, Januar Adi; Agustiningsih, Maulida Dwi; Oktaviana, Eva; Robi’atul Adawiyah, Nabila Anjani (Frontiers in Computer Science, 2025)
The digital platform’s usability is crucial for users but is often overlooked for those with visual impairments. The study aims to review and analyze the usability of platforms for users with visual impairments. The study is a Systematic Literature Review (SLR) that adapts the preferred reporting items for Systematic Reviews and Meta-Analysis (PRISMA) model to review 49 out of 137 publications from 2019 to 2023 indexed in Scopus. Key themes emerging from the analysis include accessibility, navigation, daily activities, screen division layout, and audio guidance. The success of platform implementation is evaluated using the System Usability Scale (SUS), Think Aloud, and Heuristic Evaluation. Building upon the exploration of 49 findings and categorization, a subsequent search is conducted for similar studies that can reinforce the strength of the arguments presented in the 49 studies. The analysis in the study is examined through research questions to provide a comprehensive and in-depth insight into the use of technology to enhance the quality of daily life for users with visual impairment. In addition to evaluating the success of platform implementation and popular evaluation methods, the systematic literature review explores the evolution of assistive technologies over the reviewed period and identifies emerging trends. The study delves into the ethical considerations surrounding developing and implementing technologies catering to individuals with visual impairments. The research aims to contribute not only to the usability aspects but also to the responsible and inclusive advancement of technology for users with visual impairments. In conclusion, this systematic literature review provides a comprehensive overview of the current state of usability in platforms designed for individuals with visual impairments. The findings of this study contribute valuable insights for designers, developers, and policymakers to enhance the inclusivity of platforms for users with visual impairments. Recommendations based on the identified themes aim to guide future research and development, fostering continuous improvement in usability and user experience for this often-neglected user demographic.